Textisms in EFL WhatsApp Communication: A Multimodal Study of Learner Voice, Register Awareness, and Constructivist Pedagogy - Fitrianingsih, Ihtiara (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study examines the role of textism use among Indonesian EFL learners engaged in real-time WhatsApp communication, focusing on how their linguistic behavior aligns with the principles of constructivist learning and learner accommodation. Drawing on triangulated data from chat transcripts, student-generated textism lists, and reflective surveys, the research reveals that learners are metalinguistically aware and rhetorically strategic in navigating informal and formal registers. Rather than viewing textisms as a form of linguistic degradation, this study reframes them as valuable pedagogical resources that foster creativity, voice, and contextual adaptability. Three learner profiles—pragmatic, creative, and cautious—emerged, reflecting diverse strategies in balancing expressivity with academic formality. Based on these insights, the study recommends integrating digital literacy activities, promoting multimodal writing tasks, differentiating writing instruction, fostering classroom metalinguistic dialogue, and encouraging translingual practices. These recommendations position informal digital language use as a scaffold for developing critical and flexible communicators in both academic and real-world contexts. The findings offer practical implications for EFL writing pedagogy and suggest directions for future research on digital literacy in multilingual classrooms.